2017
DOI: 10.1001/jamaophthalmol.2017.3407
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Associations of IL6 and PRG4 With Conjunctival Fibrosis After Glaucoma Surgery

Abstract: IMPORTANCE Postsurgical fibrosis is a critical determinant of the long-term success of glaucoma surgery, but no reliable biomarkers are currently available to stratify the risk of scarring. OBJECTIVE To compare the clinical phenotype of patients with conjunctival fibrosis after glaucoma surgery with candidate gene expression tissue biomarkers of fibrosis. DESIGN, SETTING, AND PARTICIPANTS In this cross-sectional study, 42 patients were recruited at the time of glaucoma surgery at the Moorfields Eye Hospital fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…21,22 Studies regarding increased fibrosis in patients with trabeculectomy failure reveal an up-regulation of the IL-6 and PRG4 gene as well as increases in VEGF and MCP-1 aqueous humor levels, although samples as small and not many inflammatory markers have simultaneously been evaluated. [23][24][25][26] Therefore, given that inflammation markers are elevated in glaucoma and have been associated with increased scarring after trabeculectomy, it is possible that higher preoperative ocular pro-inflammatory cytokine levels may determine the success of surgery. In this regard, valuable prognostic biomarkers for trabeculectomy success could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Studies regarding increased fibrosis in patients with trabeculectomy failure reveal an up-regulation of the IL-6 and PRG4 gene as well as increases in VEGF and MCP-1 aqueous humor levels, although samples as small and not many inflammatory markers have simultaneously been evaluated. [23][24][25][26] Therefore, given that inflammation markers are elevated in glaucoma and have been associated with increased scarring after trabeculectomy, it is possible that higher preoperative ocular pro-inflammatory cytokine levels may determine the success of surgery. In this regard, valuable prognostic biomarkers for trabeculectomy success could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Translocation of activated NF-κB into the nucleus can promote the expression of related genes, such as TNF-α, IL-6, IL1β, and NLRP3 [49]. These substances are reported to play an important role in the occurrence and development of fibrosis [50][51][52][53][54][55]. Research showed that Krüppel-like factor 4 (KLF4), a zinc finger transcription factor, can ameliorate chronic kidney disease through mitigating TNF-mediated tissue injury and fibrosis [50].…”
Section: Cellular Senescence and Fibrosismentioning
confidence: 99%
“…2 Lubricin is produced by numerous tissues, including the cornea, conjunctiva, trabecular meshwork, heart, lung, liver, cartilage, bone, kidney, brain, testis, placenta and small intestine. 1,[10][11][12][13][14] At these locations lubricin may act to regulate a number of processes, such as homeostasis, tissue development, shear stress, innate immunity, inflammation and wound healing. 1,[11][12][13] We hypothesize that lubricin is also synthesized and expressed by the amniotic membrane (AM).…”
Section: Introductionmentioning
confidence: 99%
“…1,[10][11][12][13][14] At these locations lubricin may act to regulate a number of processes, such as homeostasis, tissue development, shear stress, innate immunity, inflammation and wound healing. 1,[11][12][13] We hypothesize that lubricin is also synthesized and expressed by the amniotic membrane (AM). Our rationale is that this tissue possesses anti-adhesive, anti-fibrotic and antiinflammatory properties, and promotes ocular surface redevelopment and wound healing.…”
Section: Introductionmentioning
confidence: 99%